Air quality impacted by local pollution sources and beyond – Using a prominent petro-industrial complex as a study case. (May 2018) - Chen, Sheng-Po; Wang, Chieh-Heng; Lin, Wen-Dian; Tong, Yu-Huei; Chen, Yu-Chun; Chiu, Ching-Jui; Chiang, Hung-Chi; Fan, Chen-Lun; Wang, Jia-Lin; Chang, Julius S.
Abstract: The present study combines high-resolution measurements at various distances from a world-class gigantic petrochemical complex with model simulations to test a method to assess industrial emissions and their effect on local air quality. Due to the complexity in wind conditions which were highly seasonal, the dominant wind flow patterns in the coastal region of interest were classified into three types, namely northeast monsoonal (NEM) flows, southwest monsoonal (SEM) flows and local circulation (LC) based on six years of monitoring data. Sulfur dioxide (SO2 ) was chosen as an indicative pollutant for prominent industrial emissions. A high-density monitoring network of 12 air-quality stations distributed within a 20-km radius surrounding the petrochemical complex provided hourly measurements of SO2 and wind parameters. The SO2 emissions from major industrial sources registered by the monitoring network were then used to validate model simulations and to illustrate the transport of the SO2 plumes under the three typical wind patterns. It was found that the coupling of observations and modeling was able to successfully explain the transport of the industrial plumes. Although the petrochemical complex was seemingly the only major source to affect local air quality, multiple prominent sources from afar also played a significant role in local air quality. As a result, we found that a more complete and balanced assessment of the local air quality can be achieved only after taking into account the wind characteristics and emission factors of a much larger spatial scale than the initial (20 km by 20 km) study domain. Graphical abstract: Image 1 Highlights: A gigantic petrochemical complex is perceived as the major cause of local pollution. Three wind flow patterns dominate the complex-surrounded area. Cross-boundary transport can be as important as local emissions. Abstract : This work shows that the coupling of network measurements with model simulations is an effective approach with which to assess the impact of large isolated industrial emissions on air quality.